1999
DOI: 10.1016/s0002-9440(10)65407-7
|View full text |Cite
|
Sign up to set email alerts
|

DNA Copy Number Changes in Thyroid Carcinoma

Abstract: The genetic changes leading to thyroid cancer are poorly characterized. We studied DNA copy number changes by comparative genomic hybridization (CGH) in 69 primary thyroid carcinomas. In papillary carcinoma , DNA copy number changes were rare (3 of 26 , 12%). The changes were all gains , and they were associated with old age (P ‫؍‬ 0.01) and the presence of cervical lymph node metastases at presentation (P ‫؍‬ 0.08). DNA copy number changes were much more frequent in follicular carcinoma (16 of 20, 80%) than i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
59
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(81 citation statements)
references
References 45 publications
19
59
3
Order By: Relevance
“…Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines.…”
Section: Conventional Cytogenetic and Cgh Analysissupporting
confidence: 80%
See 1 more Smart Citation
“…Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines.…”
Section: Conventional Cytogenetic and Cgh Analysissupporting
confidence: 80%
“…The chromosomal gains and losses observed for each of the cell lines and respective primary tumours were represented in an excel table (CGH supplementary data). Analysis of these data allowed to verify that although CGH alterations observed in the cell lines were not identical to the ones found in primary tumours, they presented major similarities, indicating that these cell lines largely reflect their primary tumour major cytogenetic imbalances.Comparison of our PDTC and ATC CGH results with previously reported data (Hemmer et al, 1999;Wilkens et al, 2000;Wreesmann et al, 2002;Rodrigues et al, 2004) revealed that all imbalances, described as frequently occurring in the literature, were also observed in the cell lines. …”
supporting
confidence: 80%
“…Although they probably imply significant genetic changes, it is likely that they were not sufficient to cause the aggressive malignant phenotype since they occurred also in the nontumorigenic lines. It is, however, of interest that recent CGH and loss of heterozygosity (LOH) studies on follicular carcinomas [36,37] and Hürthle cell tumors [38] of the thyroid gland revealed the same aberrations (losses on chromosomes 13q and 9q31-q33, gains on chromosomes 1q and 20) as this model cell system of radiation-induced transformation of epithelial thyroid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although there are different reports of overexpression of Skp2 protein in human haematological and solid cancers (Gstaiger et al 2001, Kudo et al 2001, Latres et al 2001, Chiarle et al 2002, Masuda et al 2002, Signoretti et al 2002, Li et al 2004, so far there are no studies regarding the clinical significance or the biological behaviour of Skp2 expression in human thyroid carcinomas. Most interestingly, genetic alterations that result in gain of part or of the entire short arm of chromosome 5, where the Skp2 gene has been assigned at 5p13, frequently occur in PTC, Hurthle carcinomas and ATC (Hemmer et al 1999,Wada et al 2002, Foukakis et al 2005, suggesting that Skp2 may be the target of gene amplification in a fraction of thyroid cancer.…”
Section: Introductionmentioning
confidence: 99%